The Dynamics of Re-introduced Kihansi Spray Toad Nectophrynoides asperginis and other Amphibians in Kihansi Gorge, Udzungwa Mountains, Tanzania - Ngalason, Wilirk; Nahonyo , Cuthbert L.; Msuya, Charles A. (Tanzania Journal of Science, 2019)
The dynamics of the reintroduced Kihansi spray toad Nectophrynoides asperginis and other amphibian species that occur in the Kihansi gorge, Udzungwa Mountains were studied. The area is a home for the endemic toad that became extinct before individuals bred in captivity were reintroduced. Previous studies on the biology of amphibians conducted in the gorge focused on a few aspects but none has dealt with the dynamics of both the reintroduced Kihansi spray toad (KST) and other amphibians. Information on species richness and the abundance of amphibian species occurring in the gorge have not been dealt with in depth. Time-constrained audio-visual encounter surveys were conducted between February 2015 and May 2017 in the gorge to assess detectability rates of the reintroduced toad and other amphibian species. Sixteen species were detected including the reintroduced Kihansi spray toad. The detection rate of the KST was highest shortly after reintroduction and decreased precipitously during subsequent surveys. The results suggest low survivorship of the reintroduced KST. The detection rates of other amphibian species varied between species, although there was no significant variation in the detection rates between different sampling periods. A few species were encountered once, whereas others were encountered throughout the study period. Detection rates were influenced by the species lifestyle and weather conditions. Further studies are recommended to assess the possible causes of low survivorship of the reintroduced toads. Keywords: Kihansi gorge, Kihansi Spray Toad, Reintroduction, Survivorship